Biology unmoored : Melanesian reflections on life and biotechnology - Bamford, Sandra C., 1962- (University of California Press, 2007)
Biology Unmoored is an engaging examination of what it means to live in a world that is not structured in terms of biological thinking. Drawing upon three years of ethnographic research in the highlands of Papua New Guinea, Sandra Bamford describes a world in which physiological reproduction is not perceived to ground human kinship or human beings' relationship to the organic world. Bamford also exposes the ways in which Western ideas about relatedness do depend on a notion of physiological reproduction. Her innovative analysis includes a discussion of the advent of assisted reproductive techn.